1996
DOI: 10.1002/(sici)1099-1646(199603)12:2/3<287::aid-rrr396>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Microhabitats and Their Use by Brown Trout (Salmo Trutta) and Grayling (Thymallus Thymallus) in the River Vojmån, Sweden

Abstract: Microhabitat preferences of brown trout and grayling were studied in the upper portion of the River Vojmån, northern Sweden in 1990–1993. Microhabitat preference was quantified for open water fish during the day and at dusk and for fish residing under stones during the day. In total, measurements were made for 665 trout and 230 grayling, ranging in size from 2.5 to 50 cm total length. Relationships were found between most microhabitat variables and fish length. Consequently, fish were divided into three size g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 16 publications
3
32
0
2
Order By: Relevance
“…Previous studies have illustrated the key importance of water depth in determining juvenile brown trout habitat use (Bohlin, 1977;Bagliniere and Champigneulle, 1982;Egglishaw and Shackley, 1982;Kennedy and Strange, 1982;Heggenes, 1988c, d), including Danish small lowland streams (Hermansen and Krog, 1984). All of the above studies and others have shown that there is a positive correlation between fish size and water depth, and that the larger the trout, the deeper water it prefers (Greenberg et al, 1996;Heggenes et al, 1999;Maki-Petays et al, 1997). This preference for deep water could be explained by the possibility that parr may primarily be feeding nocturnally during summer (Alvarez and Nicieza 2003;Orpwood et al, 2006;Conallin, 2009;Conallin et al, 2012), and seeking refuge during the day to avoid predation (Aarestrup et al, 2003;Gwiazda and Amirowicz, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have illustrated the key importance of water depth in determining juvenile brown trout habitat use (Bohlin, 1977;Bagliniere and Champigneulle, 1982;Egglishaw and Shackley, 1982;Kennedy and Strange, 1982;Heggenes, 1988c, d), including Danish small lowland streams (Hermansen and Krog, 1984). All of the above studies and others have shown that there is a positive correlation between fish size and water depth, and that the larger the trout, the deeper water it prefers (Greenberg et al, 1996;Heggenes et al, 1999;Maki-Petays et al, 1997). This preference for deep water could be explained by the possibility that parr may primarily be feeding nocturnally during summer (Alvarez and Nicieza 2003;Orpwood et al, 2006;Conallin, 2009;Conallin et al, 2012), and seeking refuge during the day to avoid predation (Aarestrup et al, 2003;Gwiazda and Amirowicz, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of instream and floodplain habitat types has stimulated the evolution of species that use the habitat mosaic created by hydrologic variability. For many riverine species, completion of the life cycle requires an array of different habitat types, whose availability over time is regulated by the flow regime (Greenberg et al 1996).…”
Section: Flow Determines Habitats and Biotic Communitiesmentioning
confidence: 95%
“…This technique is most commonly used to survey juvenile salmonid populations but can also be used to assess other species groups. Snorkel survey programs have been designed and implemented so as to standardize procedures for underwater techniques to survey fish species in streams (Thurow 1994;Greenberg et al 1996;O'Neal 2007).…”
Section: Empirical and Statistical Techniques For Estimating Habitat mentioning
confidence: 99%
“…7.3). Fish were observed via snorkeling in the fully discharged sections (Thurow 1994;Greenberg et al 1996), and the abiotic characteristic (water depth, flow velocity, substrate, and cover) of used and available habitat depended on species and life stage were measured.…”
Section: Managing River Systems Through Habitat Assessmentmentioning
confidence: 99%